2012
DOI: 10.1186/1471-2458-12-824
|View full text |Cite
|
Sign up to set email alerts
|

Client characteristics and acceptability of a home-based HIV counselling and testing intervention in rural South Africa

Abstract: BackgroundHIV counselling and testing (HCT) is a critical gateway for addressing HIV prevention and linking people to treatment, care, and support. Since national testing rates are often less than optimal, there is growing interest in expanding testing coverage through the implementation of innovative models such as home-based HIV counselling and testing (HBHCT). With the aim of informing scale up, this paper discusses client characteristics and acceptability of an HBHCT intervention implemented in rural South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
2
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 22 publications
1
61
2
7
Order By: Relevance
“…The 85% rate of male partner access and couple HIV counseling and testing (HCT) found in this study is the highest reported for male partners of pregnant women and substantially higher than that reported in previous studies that used community mobilization, written invitations, couple-oriented post-test HIV counseling or home based door-to-door HCT [15, 18, 20, 28]. There was high acceptability of home-visits for couple HCT most likely due to couples HCT testing approach which provided for confidentiality and sharing of results between partners, experience and flexibility of the counsellors, and prior door-to-door home based HIV testing in the region[29].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The 85% rate of male partner access and couple HIV counseling and testing (HCT) found in this study is the highest reported for male partners of pregnant women and substantially higher than that reported in previous studies that used community mobilization, written invitations, couple-oriented post-test HIV counseling or home based door-to-door HCT [15, 18, 20, 28]. There was high acceptability of home-visits for couple HCT most likely due to couples HCT testing approach which provided for confidentiality and sharing of results between partners, experience and flexibility of the counsellors, and prior door-to-door home based HIV testing in the region[29].…”
Section: Discussioncontrasting
confidence: 56%
“…However, in at least three studies, less than 30% of testers reached through door-to-door HBCT were men and few (~4%) of the tested men were partners of women who were pregnant at the time [2022]. …”
Section: Introductionmentioning
confidence: 99%
“…Our study provides a further insight into the gender disparity in the early stages of the cascade of care. First, men were less likely than women inclined to get tested for HIV, mostly because of their absence due to labour migration, which was also found in other sites in subSaharan Africa [11,30,31]. We managed to reach 80% testing coverage among eligible men by repeating visits, including during weekends.…”
Section: Discussionmentioning
confidence: 92%
“…Earlier studies on home-based testing have proven to be acceptable and successful in rural settings. [47,48] The primary goal of HIV and AIDS prevention and control is to reduce new infections, morbidity, and mortality through early case detection and initiation of treatment. The hub of health services delivery in Rivers State has been through the formal health sector and its network of facilities.…”
Section: Discussionmentioning
confidence: 99%